Analysis of the effect of environmental conditions on energy savings in lighting systems with dimming method in campus buildings - Nazir, Refdinal; Akbar, Fajril; Malik, Hasmat; Saputra, Dendi Adi; Muharram, Igo Cikal (International Journal of Power Electronics and Drive Systems (IJPEDS), 2025)
Our research is introducing a lighting system using dimming lamps to utilize natural sunlight to save electrical energy in campus buildings. It began with designing an LED light-dimming system using AC chopper technology. It was tested in library rooms in campus buildings. Its room is divided into three zones (A, B, C) based on the intensity of natural light reaching the room and the location of the work points. We analyzed the influence of the environment around the research object, including the location of work points, weather conditions, the position of the sun, and electrical energy saving in lighting systems using dimming LED lights in campus buildings. The test results show that implementing the proposed dimming system can reduce room electricity consumption by an average of 50.31% in good weather conditions. The location of the work point in the room dramatically influences the amount of this savings. For work point locations in zone C, these savings can reach 93.707%, while for work points in zone A, the savings are only 12.177%. The results show that the percentage of electricity consumption savings from the lighting system can be increased by increasing the natural light that reaches the room.